The Effect of Family APGAR Score on Depression Rate in Type 2 Diabetes Mellitus Patients at First-Level Health Facilities - Annafsul Mutmainah; Hari Kusnanto; Oryzati Hilman (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
Background: Diabetes Mellitus (DM) is a group of degenerative diseases. The prevalence of DM is increasing from year after year. The uncontrolled blood sugar level is associated with the incidence of depression in patients with type 2 diabetes mellitus (T2DM). Additionally, depression will increase the risk of micro and macrovascular complications, disability, and mortality. A functional family is needed for the successful treatment of T2DM patients. A family function assessment should be performed by a family physician as an effort to prevent the occurrence of depression. Family APGAR scores have been widely known among family medicine practitioners as a simple and fast tool for measuring the function of a family.Objectives: To determine the effect of family APGAR scores on the level of depression in patients with T2DM in first-level health facilities.Methods: This study is a quantitative analytic research with a cross-sectional design. A total of 98 T2DM patients as research subjects were measured using family APGAR score questionnaires. The result of the statistical analysis showed a significant effect of family APGAR scores on depression, with correlation strength (-0.364). Furthermore, the research subjects underwent measurement of the depression level by using the HAD (Hospital Anxiety and Depression) scale. Linear regression analysis was used to determine the effect of the family APGAR score and other factors on the level of depression.Results: Data collection from six first-level health facilities obtained 98 samples. Linear regression statistical analysis showed that there is a significant effect of family APGAR scores and age towards the level of depression with sig < 0.05 (0.000). Family APGAR scores and age contributed 10.6% in predicting the depression in the T2DM patient. Another 89.4% is explained by other factors which were not studied in this research.Conclusion: There is a significant effect of family APGAR scores and age on the level of depression in a T2DM patient in first-level health facilities.